2003
DOI: 10.1109/jssc.2003.811973
|View full text |Cite
|
Sign up to set email alerts
|

A 14-bit high-temperature ΣΔ modulator in standard cmos

Abstract: Experimental verification is given for the use of 61 modulation for high-temperature applications ( approximately 150 C) in a standard CMOS process. Switched-capacitor circuits are used to implement a second-order single-stage and a third-order 2-1 MASH 61 modulator with single-bit quantization. The two modulators have an oversampling ratio of 256 with an input signal bandwidth of 500 Hz. The modulators were fabricated in a 1.5-m standard CMOS technology. A fully differential signal path and near minimum sized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Prior work in SOI CMOS has shown that the elimination of junction leakage can enable the operation of a variety of analog circuits at temperatures near 300 °C [1]. In bulk CMOS, an instrumentation amplifier achieved an average gain error under 25 ppm for temperatures as high as 250 °C, and 500 ppm at 300 °C [2], and a switched-capacitor (SC) 14-bit sigma-delta modulator has been functional at 255 °C [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work in SOI CMOS has shown that the elimination of junction leakage can enable the operation of a variety of analog circuits at temperatures near 300 °C [1]. In bulk CMOS, an instrumentation amplifier achieved an average gain error under 25 ppm for temperatures as high as 250 °C, and 500 ppm at 300 °C [2], and a switched-capacitor (SC) 14-bit sigma-delta modulator has been functional at 255 °C [3].…”
Section: Introductionmentioning
confidence: 99%
“…Fully differential, SC circuits are relatively invulnerable to bulk leakage current providing that the charge loss over a clock cycle is small and differentially well matched [3]. Precise transient behavior is unimportant providing that the circuitry is fully settled at the end of each clock cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Monolithic bulk CMOS circuits, including logic gates, memories, oscillators, amplifiers, and analog-to-digital convertors, have been functionally demonstrated at temperatures beyond 200 • C [12][13][14][15][16][17][18][19]. Many research groups have previously implemented high temperature interface circuits for piezoresistive and piezoelectric MEMS sensors [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…There are several available classical techniques to compensate analog circuit impairments, e.g., [1], in particular, high-temperature techniques to minimize the circuit impairments at high temperatures are discussed in [2]− [7]. Among these techniques, the constant-g m biasing is a classic and popular technique that is commonly used in commonly used circuits [1] as well as high-temperature circuits [7]− [9]. Using a temperature-stable resistor is critical for any temperaturedependent application.…”
Section: Introductionmentioning
confidence: 99%